Cinema by other means - Levi, Pavle (Oxford University Press, 2012)
Cinema by Other Means explores avant-garde endeavors to practice the cinema by using the materials and the techniques different from those commonly associated with the cinematographic apparatus. Using examples from both the historical and the post-war avant-garde -- Dada, Surrealism, Letterism, "structural-materialist" film, and more -- Pavle Levi reveals a range of peculiar and imaginative ways in which filmmakers, artists, and writers have pondered and created, performed and transformed, the "movies" with or without directly grounding their work in the materials of film.